Between padlocks and bolts: Symbolic violence against women from Neopentecostalism in Costa Rica - Vindas Benavides, Ruth (2023)
Symbolic violence against women is exercised in different spaces, such as the re-Symbolic violence against women is exercised in different spaces, such as the re-ligious one, where it goes completely unnoticed. By not viewing it as violence, it is normalized without questioning those who exercise it and rather it approves ofthem. In religious spaces, this evil causes other forms of violence in women, whichare the ones that finally come to be seen. To delve into this topic, we propose inthis article as a general objective, to investigate the impact generated by symbolic gender violence that is exerted on evangelical women through neo-Pentecostal reli-gious discourses and practices in Costa Rica. For this, the qualitative research me-thodology we use, making use of the observation technique in two neo-Pentecostal congregations in rural and urban areas and interviews with two women from each congregation. Through the results, it is possible to demonstrate from different va-riables, the forms of symbolic violence exerted from these spaces. With the results, a critical analysis is carried out from the human rights of women and from the Latin American feminist theology of liberation. We conclude that, through literal inter-pretations of biblical texts and the use of images of God elaborated from patriar-chalism, machismo and androcentrism, among others, a strong symbolic violence is exerted of which the women themselves are not aware. Hence the importance ofmaking this form of violence visible to find alternatives for overcoming it.